Super‐stable mineralization effect of layered double hydroxides for heavy metals: Application in soil remediation and perspective. Issue 2 (8th October 2021) - Kong, Xianggui; Hao, Peipei; Duan, Haohong
Abstract: Agriculture soil plays a crucial role in sustainable development of human society. Unfortunately, soil quality is continuing degradation due to industrial and agricultural activities. Among them, agriculture soil contamination by heavy metals has become a serious threat to global food safety and human health. Because of low‐cost, easy to implement, and fast effects, in situ chemical stabilization strategy has drawn great attention in soil remediation fields. However, since heavy metals are not removed from soil, it is still a great challenge to develop the cost‐effective stabilizers with strong and long‐term immobilization ability. Layered double hydroxides (LDHs) have been extensively applied in environmental fields owing to their unique structure. Very recently, LDHs have been used as amendment in in situ soil remediation for immobilization of heavy metals, exhibiting excellent long‐term stability in practice application through trapping heavy metal ions into the lattice of LDHs layer. Given that the super‐stable mineralization effect of LDHs for heavy metals, we summarize the structure of LDHs, key points of super‐stable mineralization, practical challenges, and potential applications in other heavy metals pollution scenarios in this article, wishing that could provide new strategies and insights into rational designing of amendments for soil remediation. Abstract : Owing to the super‐stable mineralization property, layered double hydroxides exhibited excellent performance in soil remediation contaminated by heavy metal ions, providing new strategies and insights into rational designing of amendments in other heavy metals pollution scenarios.